2019
DOI: 10.1155/2019/3982428
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Intravitreal Dexamethasone Implant on Vessel Diameters in Patients with Retinal Vein Occlusion

Abstract: Purpose. To investigate the vasomotor responses and diameter of retinal vessels in patients with macular edema secondary to retinal vein occlusion (RVO) who were treated with intravitreal dexamethasone implant. Methods. We enrolled 17 eyes of 17 patients with macular edema secondary to RVO. All patients were evaluated through optical coherence tomography and dynamic and static retinal vessel analysis, using the Dynamic Vessel Analyzer (Imedos, Jena, Germany) before administration (baseline) and 1 week, 1 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Apart from laser photocoagulation and intravitreal anti-VEGF agents, intravitreal steroids have been used in the treatment of macular edema secondary to RVO. Two studies that investigated the effect of an intravitreal injection of a sustained-release intravitreal dexamethasone implant (Ozurdex; Allergan, Irvine, CA, USA) in 17 and 40 eyes with RVO, respectively, found that retinal venular diameters were narrower after treatment, whereas retinal arterioles showed no response [ 20 , 21 ]. Furthermore, Eibenberger et al reported a significant decrease in retinal venules only in CRVO and not in the studied BRVO population [ 21 ], whereas Yilmaz Tugan et al demonstrated the vasoconstriction of venules in both CRVO and BRVO patients [ 20 ], showing controversial results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from laser photocoagulation and intravitreal anti-VEGF agents, intravitreal steroids have been used in the treatment of macular edema secondary to RVO. Two studies that investigated the effect of an intravitreal injection of a sustained-release intravitreal dexamethasone implant (Ozurdex; Allergan, Irvine, CA, USA) in 17 and 40 eyes with RVO, respectively, found that retinal venular diameters were narrower after treatment, whereas retinal arterioles showed no response [ 20 , 21 ]. Furthermore, Eibenberger et al reported a significant decrease in retinal venules only in CRVO and not in the studied BRVO population [ 21 ], whereas Yilmaz Tugan et al demonstrated the vasoconstriction of venules in both CRVO and BRVO patients [ 20 ], showing controversial results.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies that investigated the effect of an intravitreal injection of a sustained-release intravitreal dexamethasone implant (Ozurdex; Allergan, Irvine, CA, USA) in 17 and 40 eyes with RVO, respectively, found that retinal venular diameters were narrower after treatment, whereas retinal arterioles showed no response [ 20 , 21 ]. Furthermore, Eibenberger et al reported a significant decrease in retinal venules only in CRVO and not in the studied BRVO population [ 21 ], whereas Yilmaz Tugan et al demonstrated the vasoconstriction of venules in both CRVO and BRVO patients [ 20 ], showing controversial results. These findings could be attributed to the fact that intravitreal dexamethasone acts by stabilizing the endothelial cell tight junctions and reducing intraocular cytokine production [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the reduction was observed within the first 12 months, with 29% and 6% in the first and second 12month periods, respectively. Mean CRAE in treated eyes reduced by 10.6% to month 24 [2,3].…”
Section: To the Editormentioning
confidence: 94%